A study on prevalence of HIV infection among pregnant women attending antenatal clinic in a tertiary care hospital, Cuttack, India - Nayak, Ajit Kumar; Jain, Manju Kumari; Dhivya, S.; Hota, Sumitra (International Journal Of Community Medicine And Public Health, 2017)
Background: Estimating the HIV seroprevalence in a low risk population such as pregnant women provide essential information for monitoring trend of HIV in general population and assist in prevention from mother to child transmission. Methods: This study was conducted in SCB Medical College and Hospital, Cuttack, India between February 2014 to August 2014 which includes 1600 pregnant women who attended antenatal clinic. Blood sample collected after pretest counselling and informed consent, tested for HIV antibodies as per NACO guidelines. First antibody test was ELISA. If initial result was positive, it was confirmed by two other supplemental tests. Results: Out of 1600 pregnant women, 8 found to be HIV-positive with seroprevalence rate of 0.5%. Majority of seropositive women (87.5%) were in the age group of 20-30 Years. 12.5% were in 15-19 years of age. The seroprevalence was high in less than 20 years of age (1.9%), with higher reproductive history (2.4%), and in illiterates (3%). Majority of HIV positive women’s husband were migrants followed by truckers. Conclusions: This study indicates a marginal increase in HIV prevalence in antenatal women even though our study population is not representative of whole India because it is a hospital based study with limited sample size. Mother to child transmission of HIV infection during pregnancy, delivery or breast feeding is responsible for more than 90% of pediatrics AIDS. Proper antenatal screening, interventions and preventive strategies during pregnancy, delivery and breastfeeding will bring down the mother to child transmission of HIV.